2016
DOI: 10.2528/pierm16051806
|View full text |Cite
|
Sign up to set email alerts
|

Rf and Microwave Low Power Dielectric Heating Using Parallel Plate Applicator to Control Insect Pests on Tomato Plant

Abstract: Abstract-This paper focuses on electromagnetic exposure to control insect pests in agriculture using parallel plate applicator. A tomato plant and "Helicoverpa armigera" eggs and larvae are exposed to 915 MHz and 2450 MHz. A parallel plate applicator is fabricated and matched with Radio Frequency and Microwave source at 50 Ω. The power up to 250 W was applied to parallel plate applicator in an anechoic chamber to observe the behavior and heating effect on commodities inside the applicator. The rise in temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…For many reasons, including the complexity of the wild environment, the influence of environmental conditions, the nature of the host plant, the biology and movement, and the sensitivity of different insect life stages, there has been little investment in the development of technologies based on dielectric heating to control field insects, in addition to challenges in designing reliability into high-frequency RF and microwave systems adapted to the host plant. Only two main field insect pests have been investigated in more detail, and the other affecting high moisture content crops [ 24 ], with one impacting low MC crops [ 129 ].…”
Section: Dielectric Heating For Insect Controlmentioning
confidence: 99%
See 4 more Smart Citations
“…For many reasons, including the complexity of the wild environment, the influence of environmental conditions, the nature of the host plant, the biology and movement, and the sensitivity of different insect life stages, there has been little investment in the development of technologies based on dielectric heating to control field insects, in addition to challenges in designing reliability into high-frequency RF and microwave systems adapted to the host plant. Only two main field insect pests have been investigated in more detail, and the other affecting high moisture content crops [ 24 ], with one impacting low MC crops [ 129 ].…”
Section: Dielectric Heating For Insect Controlmentioning
confidence: 99%
“…As reported in Refs. [ 24 , 26 ], a tomato plant affected by H. armigera is placed between the two parallel electrodes and exposed to a power of 250 W at 2.45 GHz and 915 MHz, with early egg hatching observed after 10 min of treatment, resulting in disturbance of the insect pest's life cycle. Interestingly, the study findings showed that the power level at 250 W used in the microwave treatment did not significantly affect the different H. armigera larval instars at either frequency ( Table 24 ).…”
Section: Dielectric Heating For Insect Controlmentioning
confidence: 99%
See 3 more Smart Citations